Imagining Outer Space
XXXIII, 443 p. 63 illus., 37 illus. in color.
Keywords: Imagining Outer Space makes a captivating advance into the cultural history of outer space and extraterrestrial life in the European imagination. How was outer space conceived and communicated? What promises of interplanetary expansion and cosmic colonization propelled the project of human spaceflight to the forefront of twentieth-century modernity? In what way has West-European astroculture been affected by the continuous exploration of outer space? Tracing the thriving interest in spatiality to early attempts at exploring imaginary worlds beyond our own, the book analyzes contact points between science and fiction from a transdisciplinary perspective and examines sites and situations where utopian images and futuristic technologies contributed to the omnipresence of fantasmatic thought. Bringing together state-of-the-art work in this emerging field of historical research, the volume breaks new ground in the historicization of the Space Age.